The Impact of COVID-19 Pandemic on Long-Term Care Facilities Worldwide: An Overview on International Issues - Thompson, Dana-Claudia (Biomed Res Int, 2020)
The COVID-19 pandemic had a great negative impact on nursing homes, with massive outbreaks being reported in care facilities all over the world, affecting not only the residents but also the care workers and visitors. Due to their advanced age and numerous underlying diseases, the inhabitants of long-term care facilities represent a vulnerable population that should benefit from additional protective measures against contamination. Recently, multiple countries such as France, Spain, Belgium, Canada, and the United States of America reported that an important fraction from the total number of deaths due to the SARS-CoV-2 infection emerged from nursing homes. The scope of this paper was to present the latest data regarding the COVID-19 spread in care homes worldwide, identifying causes and possible solutions that would limit the outbreaks in this overlooked category of population. It is the authors' hope that raising awareness on this matter would encourage more studies to be conducted, considering the fact that there is little information available on the impact of the SARS-CoV-2 pandemic on nursing homes. Establishing national databases that would register all nursing home residents and their health status would be of great help in the future not only for managing the ongoing pandemic but also for assessing the level of care that is needed in this particularly fragile setting.